divide the sum of minus 3 by 7 and 5 by 6 from their product
Answers
Answered by
7
Answer:
Step-by-step explanation:
The sum of the number
==>
-3/4+5/6
==>
Lcm4,6= 12
==>
(-3×3 + 5×2) / 12
==>
(-9 +10)/ 12
==>
1/12
The product of number
==>
(-3/4) × (5/6)
-15/24 => -5/8
The divide the sum by it's product value
==>
( 1/12 ) ÷ -5/8
==>
(1/12) × -8/5
==>
-8/60
==> -2/15 Ans
It's helpful for you
Similar questions
Computer Science,
6 months ago
Social Sciences,
6 months ago
Biology,
6 months ago
Science,
1 year ago
Biology,
1 year ago